Reconstitution of the Oral Sphincter - Chowdhury, Siti Royh (Indian Journal of Plastic Surgery, 1987)
The result in a fourteen year old female child with macroglossia and lax oral sphincter who was treated successfully by glossectomy and free palmaris longus muscle grafts for reconstituting the oral sphincter is being presented.